Genetic diversity of Fusarium solani isolates from black pepper (Piper nigrum L.) in Malaysia by ISSR marker - Shahnazi, Sahar; Meon, Sariah; Vadamalai, Ganesan; Yazdani, Darab; Shabanimofrad, Mahmoodreza (Universiti Putra Malaysia Press, 2014)
For effective management and control of yellowing disease, inter-simple sequence repeat (ISSR) markers were employed to investigate genetic diversity among 34 isolates of Fusarium solani, which had been isolated from major growing areas of black pepper in Malaysia. Over 15 primers, with fragment sizes ranging from 200 bp to 3600 bp, and a total of 253 amplified loci were amplified in all 34 isolates, with an average of 17 bands per primer; among which 248 (98.02 %) were polymorphic. High genetic diversity at species level was revealed (Nei’s gene diversity h = 0.2671 and Shannon information index I = 0.4134, respectively). Sarikei population was found to have a higher degree of polymorphism compared to other populations. The dendrogram generated from UPGMA cluster analysis categorized the 34 F. solani isolates into two major clusters based on Jaccard’s similarity coefficients. Cluster I contained a unique isolate. Cluster II contained 33 isolates which were split into two different subclusters. Results showed that the clusters were not related to geographic origins. Meanwhile, ISSR fingerprinting generated highly polymorphic markers that could be used to study genetic characterization of F. solani and to clarify phylogenic relationships, as well as useful for efficient management of yellowing disease and finding breeding programmes to find cultivars of black pepper that are resistant to F. solani.